Rancang Bangun Sistem Pemilah Tomat Berdasarkan Tingkat Kematangan - Lb Novendita Ariadana; Dahnial Syauqy; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In human life is heavily dependent on agriculture. To meet the needs of everyday human life then takes the process of planting, harvesting and land sports. For a short time as well as the limitations of power is a challenge that must be faced by the farmers. So did the problems facing tomato farmers who must sort out the tomato based on a different level of maturity - different. Tomato growers should be picking tomatoes first and then sort it based on the level of ripeness. This is done because each level of maturity tomatoes have different uses. Of the matter, the author makes a tomato based parser system level of maturity. Level of maturity is detected using the color tomato. To detect the color of the tomatoes then it needs three sensors on the left side, top, and right system. Tomato fruit is placed in the middle of the system on the box then motor stepper will push it so it just below the sensor. Then the color of tomatoes will be read by a third color sensor. After that the Bayes method will look for opportunities and will classify the tomatoes into three categories. After that the system will drain the tomatoes into the container according to the degree of ripeness by opening and closing the line using a servo motor. This research has as many as 45 data training data and each level has 15 kematangn data. The result of the test there is a 10 x 9 x 1 x and correct errors. From these tests can noted that 90% of system accuracy.